2022
DOI: 10.1021/acs.est.1c08185
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Translocation of a Silica Nanocarrier and an Encapsulated Organic Pesticide Following Foliar Application in Tomato Plants

Abstract: Pesticide nanoencapsulation and its foliar application are promising approaches for improving the efficiency of current pesticide application practices, whose losses can reach 99%. Here, we investigated the uptake and translocation of azoxystrobin, a systemic pesticide, encapsulated within porous hollow silica nanoparticles (PHSNs) of a mean diameter of 253 ± 73 nm, following foliar application on tomato plants. The PHSNs had 67% loading efficiency for azoxystrobin and enabled its controlled release over sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…The fungicide azoxystrobin was reported to translocate in 2 days from a leaflet of tomato to other parts of the plant: 19% to stem, 10% to youngest leaves, 4% to mature leaves and 2% to the root 23 . When [ 14 C]cymoxanil (anti‐oomycete fungicide) was applied to the root of potted tomato plants, 75% and 90% of the label reached the shoot in 1 and 16 h respectively, but when applied to a leaf only 5% of the label reached the other parts of the plant 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungicide azoxystrobin was reported to translocate in 2 days from a leaflet of tomato to other parts of the plant: 19% to stem, 10% to youngest leaves, 4% to mature leaves and 2% to the root 23 . When [ 14 C]cymoxanil (anti‐oomycete fungicide) was applied to the root of potted tomato plants, 75% and 90% of the label reached the shoot in 1 and 16 h respectively, but when applied to a leaf only 5% of the label reached the other parts of the plant 24 .…”
Section: Discussionmentioning
confidence: 99%
“…22 The fungicide azoxystrobin was reported to translocate in 2 days from a leaflet of tomato to other parts of the plant: 19% to stem, 10% to youngest leaves, 4% to mature leaves and 2% to the root. 23 When [ 14 C]cymoxanil (anti-oomycete fungicide) was applied to the root of potted tomato plants, 75% and 90% of the label reached the shoot in 1 and 16 h respectively, but when applied to a leaf only 5% of the label reached the other parts of the plant. 24 The non-systemic fungicide fludioxonil was recently reported 25 to control Fusarium T4 in banana by foliar spray of fludioxonil-loaded glycine methyl ester-conjugated polysuccinimide nanoparticles (PGA) nanoparticles (FLU@PGA).…”
Section: Discussionmentioning
confidence: 99%
“…Plants were sampled sacrificially 2 and 5 days after foliar application of NPs and their dry weights were comparable between the two treatments ( p > 0.05, t test, Table S1). Two and 5 days were selected as sampling times as this provided the appropriate time bracket to demonstrate particle uptake, translocation and dissolution processes in the plant, and 5 days was required to reach sufficient concentrations of Si in the petiole for mass spectrometry imaging. ,, For each treatment, a total of nine plant replicates were maintained. To measure the total Zn and Si concentrations (with ICP-OES) and particle size distribution in different plant parts (spICP-MS), triplicate samples were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Mesoporous silica NPs (MSNs) have been proposed as an efficient vehicle for the delivery of chemicals to plants, because upon their uptake plants may slowly dissolve and assimilate Si into their structural tissues enhancing stalk rigidity, disease resistance, and crop yield, and as well because of their high biocompatibility, and controlled-release properties. Our prior study showed that the addition of a mesoporous silica shell enabled significant uptake and translocation of ZnO NPs in tomato plants following foliar application, whereas uptake of bare ZnO NPs was negligible . Compared to the foliar application with conventional Zn 2+ (supplied as a ZnCl 2 solution), ZnO@MSN did not result in the scorching of a leaf that was caused by ZnCl 2 , a hygroscopic salt.…”
Section: Introductionmentioning
confidence: 99%
“…Star polymer based nanocarriers with different sizes, charges, and hydrophobicity also had high (∼100%) uptake and up to ∼30% total translocation away from the leaf after foliar exposure . Approximately 100 nm polypeptide nanoparticles and polymer functionalized carbon nanotubes have delivered nucleic acids into specific cell organelles such as the cell nucleus and chloroplasts to transfect plants after foliar application. , Mesoporous silica nanoparticles have delivered micronutrients and active ingredients into tomato plants with significant (∼20%) phloem loading and translocation. , These studies all indicate that foliar applied nanomaterials can pass through physical barriers in plants and potentially achieve higher agent delivery efficiency compared to conventional agrochemical application techniques …”
Section: Introductionmentioning
confidence: 93%